Reviewing the Approach of Contemporary Islamic Teachers: An Analysis of Spirituality in General Public Education - Anwar, Moh. Kasyfil; Fanani, Zainuddin (Lembaga Yasin AlSys, 2025)
This study explores the approach of contemporary Islamic educators in delivering spiritual education to the general public, particularly in response to the challenges posed by modernity, including secularism, materialism, and hedonism. These trends have contributed to the erosion of religious authority, reducing it to a symbolic formality, and while religious affiliation has grown quantitatively, the depth of spiritual engagement has not shown corresponding development. This phenomenon is partly attributed to the inability of educators to engage the spiritual dimensions of their audiences effectively. Employing a qualitative-descriptive method grounded in literature review, this study examines the spiritual educational philosophy of al-Ghazālī as a foundational reference in Islamic pedagogy. Al-Ghazālī advocates for an integrative model of education that harmonizes reason, Islamic law (sharia), and Sufism, emphasizing the purification of the soul as a prerequisite for meaningful learning. The analysis reveals that al-Ghazālī's educational paradigm offers relevant solutions to contemporary spiritual disconnection, providing a framework capable of addressing the inner dimensions of individuals in modern society. Consequently, his approach presents a viable alternative for enhancing the spiritual quality of public religious education in the current era.